PENGARUH KEMANDIRIAN BELAJAR TERHADAP HASIL BELAJAR MATEMATIKA SISWA SMP NEGERI 2 TANO TOMBANGAN ANGKILA - Tri Fousa Pasaribu; Adek Nilasari Harahap; Alvi Sahrin Nasution (JURNAL MathEdu (Mathematic Education Journal), 2022)
This thesis discussed the effect of independent learning on mathematics learning outcomes in grade VII SMP Negeri 2 Tano Tombangan Angkola. This research is a quantitative research method of non- experimental variabel studied, namely student X learning independence and Y mathematics learning outcomes. The purpose of this study was to determine the effect of independent learning (X) on mathematics learning outcomes (Y) of student at SMP Negeri 2 Tano Tombangan Angkola. The sampel used was 30 students, while data collection was carried out by means of a questionnaire and essay test for students with the subject of the set Based on the t-test analysis thitung of 11.49 and the ttabel value is 2,048. Means thitung is greathes than ttabel (11,49 > 2,048) this means that reject Ho accept H1 or there is a sigmificant direct influence between independent learning on mathematics learning outcomes of VII grade student of SMP Negeri 2 Tano Tombangan Angkola with a coefficient of determination of 82,7% the remaining 17,3 % is influenced by other factors not examined.